PENGEMBANGAN COMPANY PROFILE BERBASIS WEBSITE PADA SEKOLAH MENENGAH KEJURUAN SWASTA YP 17 CILEGON MENGGUNAKAN FRAMEWORK LARAVEL - Fahram, Muhammad Khaidir; Gustina, Gustina; Kusuma, Vina Vijaya; Hammada Purnama, Gladys (Journal of Innovation And Future Technology (IFTECH), 2024)
Media information websites that already exist at SMKS YP 17 Cilegon have not gone well due to a lack of accurate content and information. Hence, the delivery of information at SMKS YP 17 Cilegon is still manual, such as using banners and brochures. Therefore, Vocational High School YP 17 Cilegon requires media information that is fast, precise, and interesting without having to go to school and can be accessed online by the broader community in order to obtain accurate information. The method used in this study is the waterfall method by analyzing data obtained from the school and then developing a company profile website for Vocational High School YP 17 Cilegon the design used to create this company profile website uses the PHP programming language and one of them is. from PHP frameworks. (Hypertext Preprocessor), namely Laravel, for the database the author uses MySql. The results of this study are to make it easier for students, teachers, and the wider community to get information quickly and accurately.